Presynaptic inhibition of excitatory synaptic transmission mediated by alpha adrenergic receptors in area CA3 of the rat hippocampus in vitro - Scanziani, M (J Neurosci, 1993)
We have investigated the action of norepinephrine (NE) on excitatory synaptic transmission in the hippocampus by recording from CA3 pyramidal cells in organotypic slice cultures. NE (5 microM) was found to decrease the amplitude of pharmacologically isolated EPSPs elicited with stimulation of mossy fibers or recurrent axon collaterals (mean decrease in EPSP amplitude, 44%). Desensitization was observed with repetitive applications. NE did not affect the sensitivity of CA3 cells to iontophoretically applied AMPA, and did not affect the amplitude distribution of TTX-resistant, miniature excitatory synaptic currents. These data suggest that NE acts at presynaptic receptors to decrease glutamate release. This action of NE was blocked by the alpha receptor antagonist phentolamine and the specific alpha 1 receptor antagonist prazosine, but not by the beta receptor antagonist timolol or the alpha 2 receptor antagonist idazoxan. Inhibition of EPSPs by NE was prevented by pretreatment of cultures with pertussis toxin, indicating that G- proteins couple these receptors to their effectors. Stimulation of protein kinase C with phorbol ester blocked the action of NE on EPSPs. This effect, as well as the desensitization of NE responses, was reduced by application of the protein kinase inhibitor staurosporin. Presynaptic inhibition of excitatory synaptic transmission, mediated by alpha adrenergic receptors, represents a novel modulatory action of NE in the hippocampus.